THE STRATEGIC ROLE AND FUNCTIONS OF THE CHIEF FINANCIAL OFFICER IN EFFECTIVE CORPORATE MANAGEMENT - Butabayev Mehriddin Shakhobiddinovich; Ganiev Bexruz Ikhtiyorovich (Modern American Journals, 2025)
In the modern business environment, the success of corporate governance is increasingly tied to the strategic role of the Chief Financial Officer (CFO). The CFO not only ensures financial discipline but also plays a central role in shaping long-term development strategies. This paper analyzes the multi-functional role of the CFO within corporate governance systems and discusses their influence in decision-making processes and strategic planning. The research uses a qualitative approach based on literature review and comparative analysis to determine the CFO’s contribution to financial stability and organizational efficiency.
Keywords: Chief Financial Officer, corporate governance, financial management, strategic decision-making, budgeting, investment analysis, financial planning, risk management, corporate efficiency, financial sustainability.